The 'third mission' of the university, knowledge transfer and knowledge societies. An approach from pedagogy - José Manuel Touriñán López (Universidad de La Rioja, 2020)
The notion of an information society is based on technological progress. In the knowledge society, science becomes a matter of State and knowledge is regarded from the perspective of productive development of a social, cultural and economic nature. For UNESCO, the fact of referring to societies, in the plural, expresses the explicit intention of rejecting the uniqueness of a model that does not sufficiently take into account cultural and linguistic diversity, the only element that allows us all to recognize ourselves in the changes that are currently being made. In the European Union, the growth of knowledge with productive value implies assuming the triangle of knowledge that takes as bases of work, education, research and innovation. They are the three pillars of the triangle of knowledge in the knowledge society. The third mission of the University means that it institutionally assumes the triangle of knowledge from two mains objectives: on the one hand, the institutional social responsibility of the university; and, on the other hand, the commitment to become knowledge into economic value, focusing on competitiveness and facilitating innovation, creativity and cultural, social, scientific and technological development. Education, innovation and research are related in the university and the transfer of created knowledge in the university becomes a strategic objective. However, when we talk about transfer (knowledge transfer), we are not talking about the application of my knowledge but finding effective ways to create a need for that application or to show that need to the recipients of the transfer network. This is something new that we must learn to do, individually, in some cases, and collectively, as a faculty, in others, because the knowledge transfer is not the same in any area and discipline. From the perspective of Pedagogy, the domain of the transfer function is not achieved automatically, it requires training, investment and reformulation of the functions of university professors.